(untitled) (Ex Chordis, 2023)
The aim of this paper is to analyze the Chamber and Solo works for Strings by Francesco Ricupero, a musician and composer from Naples who lived in the second half of the Eighteenth Century. Although little is known about his life, we possess a large number of his musical manuscripts. Studying and analyzing unknown manuscripts and compositions can be beneficial not only for expanding the repertoire of an instrument but also for reviving forgotten performance practices and hidden styles. Even if it is a secondary production by a forgotten composer in the history of music, it turns out to be very interesting, full of music ideas, and different from what was written and composed in Naples in the second half of the Eighteenth Century. This production deserves more attention and should be the subject of further studies, critical editions, and performances in modern times. Specifically, the Sonata for Violin and Harpsichord is the main focus of this paper. It is a unique piece composed of only two movements, which deviates from the solo repertoire of the time.